Treatment of metronidazole pharmaceutical wastewater using pulsed switching peroxi-coagulation combined with electro-Fenton process - Yongjun Liao; Yongbei Ye; Xindi Chen; Haoran Xin; Shuyue Ma; Songwei Lin; Haiping Luo (Water Cycle)
The aim of this study was to investigate the metronidazole (MNZ) degradation and real MNZ pharmaceutical wastewater treatment in the pulsed switching peroxi-coagulation (PSPC) process. Different pulsed switching frequencies and running times of H2O2 and Fe2+ productions were tested in the PSPC process. Results demonstrated that MNZ removal of 96.9 ± 1.2 % was realized in the PSPC process with a 200 mg/L MNZ and 0.1 M Na2SO4 solution within 80 min under a pulsed switching frequency of 6s: 1s and a current density of 20 mA/cm2 (H2O2) and 20 mA/cm2 (Fe2+). High MNZ removal could be attributed to efficient •OH production with the highest •OH concentration reached 321 ± 15 μM in the PSPC process. The hydroxyl and carboxyl groups of MNZ were sequentially oxidated by •OH and mineralized based on seven identified intermediates during the MNZ degradation. However, only 56.9 ± 6.7 % of COD was removed in the real MNZ wastewater treatment by the PSPC process within 90 min. A PSPC combined with electro-Fenton (EF) process was developed to enhance the COD removal in the MNZ wastewater. With MNZ wastewater as electrolytes, 3.3 ± 0.3 g/L of H2O2 was produced in a conventional EF reactor. The final COD removal reached 86–90 % using the mixture of effluent from the PSPC, the anode, and cathode chambers of the EF reactor, resulting in less than 80 mg/L COD in the effluent. Results from this study should provide a useful way to enhance real MNZ pharmaceutical wastewater treatment.